Program Peningkatan Resiliensi Bagi Pecandu Narkoba: Pendekatan Riset Tindakan Berbasis Kualitatif - Irfan Aulia Syaiful; Dearly Dearly (Universitas Islam Indonesia, 2015)
This study aimed to create a draft program to improve the resilience potential of a drug addict who is in the rehabilitation process. Resilience according to Wagnild (2009) is the ability of individuals to be able to successfully cope with adversity and change in life. Almost all people have difficulty and fall in the course of life, but they have the resilience to bounce and move on. The ability to get up and continue this life is called resilience. This study is a qualitative research based on action research with descriptive approach. This study is a problem-solving approach according to Mckay and Marshall (2001). To obtain the data, researchers used interviews and observation methods. Results of this study in the form of a draft program to improve the resilience of drug addicts are based on the theory and the data obtained from interviews and observations of the subject.Keywords: Resilience, drug addict, intervention program, action research